Microbial Diversity of Upland Rice Roots and Their Influence on Rice Growth and Drought Tolerance - Zhiqiang Pang (Microorganisms, 2020)
Among abiotic stresses, drought is one of the most important factors limiting plant growth. To increase their drought tolerance and survival, most plants interact directly with a variety of microbes. Upland rice (Oryza sativa L.) is a rice ecotype that differs from irrigated ecotype rice; it is adapted to both drought-stress and aerobic conditions. However, its root microbial resources have not been explored. We isolated bacteria and fungi from roots of upland rice in Xishuangbanna, China. Four hundred sixty-two endophytic and rhizospheric isolates (337 bacteria and 125 fungi) were distributed. They were distributed among 43 genera on the basis of 16S rRNA and internal transcribed spacer (ITS) gene sequence analysis. Notably, these root microbes differed from irrigated rice root microbes in irrigated environments; for example, members of the Firmicutes phylum were enriched (by 28.54%) in the roots of the upland plants. The plant growth-promoting (PGP) potential of 217 isolates was investigated in vitro. The PGP ability of 17 endophytic and 10 rhizospheric isolates from upland rice roots was evaluated under well-irrigated and drought-stress conditions, and 9 fungal strains increased rice seedling shoot length, shoot and root fresh weight (FW), antioxidant capability, and proline (Pro) and soluble sugar contents. Our work suggests that fungi from upland rice roots can increase plant growth under irrigated and drought-stress conditions and can serve as effective microbial resources for sustainable agricultural production in arid regions.